Anti-Inflammatory and Anti-Oxidative Effects of AM404 in IL-1β-Stimulated SK-N-SH Neuroblastoma Cells - Matthias Apweiler (Frontiers Media S.A., 2021)
An emerging number of studies address the involvement of neuroinflammation and oxidative stress in the pathophysiology of central nervous system (CNS) disorders such as depression, schizophrenia, anxiety, and neurodegenerative diseases. Different cytokines and molecules, such as prostaglandin (PG) E2, are associated with neuroinflammatory processes. The active acetaminophen metabolite AM404 has been shown to prevent inflammation and neuroinflammation in primary microglia and organotypic hippocampal slice cultures. However, its effects on pathophysiological conditions in the CNS and especially on neurons are still poorly understood. In this study, we therefore evaluated the effects of AM404 and acetaminophen on the arachidonic acid cascade and oxidative stress induced by interleukin (IL)-1β in human SK-N-SH neuronal cells. We observed that AM404 and acetaminophen significantly and concentration-dependent inhibited IL-1β-induced release of PGE2, independent of cyclooxygenases (COX)-1 and COX-2 enzymatic activity as well as COX-2 mRNA and protein levels in SK-N-SH-cells. The reduction of IL-1β-induced PGE2-release by AM404 and acetaminophen treatment might be mediated by the 8-iso-PGF2α pathway since IL-1β-induced synthesis of this free radical marker is dose-dependently reduced by both compounds, respectively. Therefore, understanding of the potential therapeutic properties of AM404 in neuroinflammation and oxidative stress might lead to future treatment options of different neurological disorders.